Extracorporeal cardiopulmonary resuscitation successfully used in a two-hour cardiac arrest caused by fulminant myocarditis: a case report - Hu, Qinxue; Liu, Xing; Wen, Chengli; Mei, Songtao; Lei, Xianying; Xu, Tao (Frontiers in Cardiovascular Medicine, 2024)
Fulminant myocarditis (FM) is characteristically associated with rapid progressive decline in cardiac function and high mortality, with rapid onset of hemodynamic dysfunction and severe arrhythmias. In this report, we describe a case concerning a patient clinically diagnosed with FM, marked by rapid progression leading to intractable ventricular fibrillation and subsequent cardiac arrest. Conventional cardiopulmonary resuscitation (CCPR) was performed 120 min before extracorporeal membrane oxygenation (ECMO) was initiated. This critical situation was effectively addressed through the utilization of extracorporeal cardiopulmonary resuscitation (ECPR). By providing sustained cardiopulmonary support, effective hemodynamics were obtained. Eventually, the patient made a full recovery, and discharged without neurologic complications on hospital day 13.